An Identification Of Modal Auxiliaries In The Articles Of “The Jakarta Post” With Regard To Corona Virus Issue - Siti Sopiah; Sri Intan Nurfitriani (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This research reports types of modal auxiliaries used and which modal auxilaries that used as the first dominant. The data are eleven articles that are only written by Esther Samboh and only discuss corona virus issue. This research collects and analyzes the data descriptively. It is found that there are three types of modal auxiliaries found, they are pure modal, special modal and semi modal. From the three types of modal, the first is pure modal which include “can-could”, “may-might”, “should”, “will-would”, and “must”. Meanwhile, The most dominant types is pure modal contains 162 clauses (19%), followed by semi modal contains of 19 clauses (2%), and special modal only includes 1 clauses (0.1%). In addition, the data shows that will becomes the first dominant type. This implies that the writer tends to put predictions more to her articles than possibility, ability, and obligation. This fact implies that the writer tends to put predictions more to her articles than possibility, ability, and obligation.